The deleterious effect of missense mutations on pre-mRNA splicing - Gonçalves, Vânia (2011)
The presence of missense mutations detected during genetic testing makes it difficult to classify their pathogenic effect. It is possible that the predicted amino acid change affects protein function; however, it is also possible that a missense mutation does not act at the protein level but rather at the nucleotide level by interfering with the correct assembly of the pre-mRNA splicing machinery. In this chapter we describe that short 6 to 9 nucleotides-containing sequence motifs act as exonic splicing regulatory elements. They are specifically recognized by corresponding splicing factors, which then assist in the recognition of the conserved splice site motifs by the spliceosome. Many examples show that a point mutation in these exonic splicing regulatory elements is sufficient to change splicing factor binding, which impairs inclusion of an exon during the splicing reaction. Thus, the molecular consequence of a missense mutation can be exon skipping and thus cause a frameshift in the messenger RNA that results in a premature stop codon and loss of function of the affected allele. Although several bioinformatic tools exist to predict splicing factor binding to mRNA, this effect of a missense mutation on splicing cannot yet be accurately predicted by sequence analysis alone. In order to determine whether a missense mutation has a deleterious effect on splicing of the corresponding mRNA, experimental analysis with either patient RNA or splicing reporter minigenes is required.